Exploring Students' Perceptions and Influences in Teaching Translation Through Qualitative and Quantitative Standards - Merahi , Abdelkrim; Makhlouf, Abdelkader; Tamimi , Yasser (Future Science, 2024)
The present study addresses the multifaceted aspects of teaching translation by investigating students' perceptions and influences, considering both qualitative and quantitative standards. It explores the contributions of these standards to the translation teaching process and evaluates the predictive capability of quantitative standards. Focusing on 183 male and female students from Saida and El-Bayah Universities, the study used a questionnaire to collect data and statistical analysis using SPSS techniques. The findings showed a positive correlation between students' perceptions of teaching translation and both qualitative and quantitative standards. Furthermore, these standards were found to make significant contributions to teaching translation, indicating that teaching translation may be predicted using quantitative criteria. The study offers insightful information that can be used for enhancing translation programs, creating engaging learning environments, and improving teacher training in diverse educational contexts.